2009
DOI: 10.1007/s11164-008-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A reactions with hydroxyl radicals: diverse pathways determined between deionized water and tertiary treated wastewater solutions

Abstract: The oxidative reactions of bisphenol A (BPA) with radiolytically generated hydroxyl radicals were studied in both deionized water and tertiary treated wastewaters. In deionized water, bisphenol A reacts with the hydroxyl radical by addition to the aromatic ring, k = 6.9 9 10 9 (±0.2) M -1 s -1 , to eventually form the prominent, long-lived, hydroxylated intermediate product. In contrast, in tertiary treated water solutions, although the initial hydroxyl radical addition reaction occurs, the hydroxylation is av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…While the reaction rate constant for the OH with BPA falls in the predicted range for aromatic compounds ((6.970.2) Â 10 9 M À1 s À1 ), the hydroxyl radical-mediated removal of BPA in high-purity water measured in steady state radiolysis experiments occurs with only 76% efficiency (Peller et al 2009). The removal efficiency is defined as the number of contaminant molecules destroyed per 100 hydroxyl radical reactions generated in solution.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…While the reaction rate constant for the OH with BPA falls in the predicted range for aromatic compounds ((6.970.2) Â 10 9 M À1 s À1 ), the hydroxyl radical-mediated removal of BPA in high-purity water measured in steady state radiolysis experiments occurs with only 76% efficiency (Peller et al 2009). The removal efficiency is defined as the number of contaminant molecules destroyed per 100 hydroxyl radical reactions generated in solution.…”
Section: Introductionmentioning
confidence: 95%
“…For example, the initial step of OH reactions often involves addition to an electron-rich site. In the case of aromatic contaminants such as bisphenol A (BPA), the hydroxyl radical adds to an aromatic ring to form a transient cyclohexadienyl radical (as shown in Figure 1), which is readily detected using transient UV absorption (Peller et al 2009). The time-dependent changes in the transient absorption spectra provide insight into the subsequent chemistry that occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivities in DMF for cyclohexenol and cyclohexenone were found to be 37.19 and 62.81%, respectively. Analyses of insitu-generated peroxide in reaction media have been the area of major interest [24][25][26]. The starch iodide paper test was performed to check the presence of peroxide.…”
Section: Effect Of O 2 and Solvent On Reactionmentioning
confidence: 99%
“…Currently, polycarbonates and epoxy resins are pervasively used to manufacture parts or bodies of various household and technological equipment such as supermarket food-wrappers, compact disks, soft drink bottles, electronic appliances, computers, furniture, auto-parts, machineries, and plastic pipes, to mention some (Burridge 2003;Saal and Hughes 2005). However, bisphenol A (BPA) possesses a similar partial chemical structure with the estrogen hormone, it exhibits affinity toward the estrogen receptor (Xu et al 2007), and has been identified as an endocrine disrupting chemical (Peller, Mezyk, and J. Cooper 2009). There is no doubt that BPA and its derivatives in the materials of the containers and wrappers of the food and drinks make their way into consumers' body fluid and the environment due to their high solubility in oils=fats and, to some extent, in water (Kuch and Ballschmiter 2001;Stuart et al 2005;NTP 2008).…”
Section: Introductionmentioning
confidence: 99%